Nutrition and Immunity: Laboratory and Clinical Aspects - Amati, L.; Cirimele, D.; Pugliese, V.; Covelli, V.; Resta, F.; Jirillo, E. (Current Pharmaceutical Design, 2003)
It is well known that inappropriate nutrient intake accounts for the maintenance of the immunological equilibrium, in humans and animals. Vitamins, elements, lipids, proteins and nucleic acids play an important role in the regulation of cellular and humoral immune responses since single or multiple deficits of these food components have been shown to cause immune abnormalities. For instance, in the course of protein-calorie malnutrition bacterial and / or viral infections represent the major cause of death. Ageing is characterized by a decline of many immune functions, and this process is called immunosenescence. Here, we report novel findings on the inability of superantigens to activate old CD8+, natural killer and B cells, as an expression of cell amnesia. In the elderly, this lack of activation could lead to lethal effects in the case of severe staphylococcal infections. Quite interestingly, recent findings outlined some similarities between human immune deficiency virus (HIV)-1 infection and ageing in terms of immune changes. The model of HIV-infection may be useful for the interpretation of ageing mechanisms and possible therapeutical interventions. Finally, the role of nutrition in different pathological conditions and the use of medical foods for correcting of immune deficits will be described.
Keywords: Immunity